PENGARUH PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMP NEGERI 5 BANJARBARU - Nizami, Ahmad Wafa; Ramadhan, Mufti; Nazif, Ahmad; Dewi, Dewi (Program Studi PAI STAI Al Falah Banjarbaru, 2021)
Abstract: In changing learning from conventional to online there are many obstacles faced by both teachers and students, the obstacles are internet network problems, quota, and tools such as laptops and cellphones as tools for conducting online learning. The population in this study was students from classes VIII and IX, 60 respondents were taken using the Stratified Sampling technique. This technique is used when the population consists of different levels, while selecting samples from each level in the population uses the Proportional Ramdom Sampling technique. Based on the results of the research that the author has carried out, it can be seen that the online learning carried out by SMP Negeri 5 Banjarbaru has the '